Collaboration Meeting with PICKSUM Malaysia - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 6 July 2021 - This collaboration was held on 6 July 2021 virtually, between FK and PICKSUM Malaysia